LITERATURE ANALYSIS ON THE STUDY OF THE PHYSIOLOGY OF THE COTTON PLANT - Shahnoza Erdanayeva; Muhayyo Boltayeva (Web of Journals Publishing, 2024)
This article provides information on the physiological characteristics of the cotton plant, analysis of studies on the use of species, botanical description, characteristics, and cultivation technology
Keywords: Cotton, genus, species, physiological, biological, subgroup, anatomical, organic, infectious, gossypol.